Upaya Preventif terhadap Konflik Masyarakat dalam Perspektif Ali Jum’ah - Rizki Azalia (Fakultas Dakwah IAIN Jember, 2020)
The Arab Spring is an interesting discussion for researchers to study. Starting with the fall of Tunisia, then Egypt, and Libya, then came the Islamic State of Iraq and Syria (ISIS) which later changed its name to the Islamic State (IS) in order to attract followers from all over the world. Such slander is not only happening in the Middle East. In Europe, precisely in France there was a bomb attack on Friday, 13 November 2015. In 2019, Brenton Tarrant killed 51 people and injured 40 people in two mosques in New Zealand. Furthermore, there was a recent bomb attack in front of the Makassar Cathedral Church on Sunday, March 28, 2021. The current study employs a library research method. The primary sources were taken from the Qur'an, the Kutub Al-Sittah (the six books), and from the works of Ali Jum'ah. Meanwhile, the secondary sources were taken from the books of tafsir and the syurūh of hadith. The results of this study revealed that in Ali Jum'ah's perspective, there are three preventive attempts to be used against slander. One of which is to imagine the Prophet as our father. According to Ali Jum'ah, by imagining Rasulullah as a father, then we are likely to feel his presence all day and night. The second attempt is to always remember Allah (through dhikr). Ali refers to the opinion of al-Ṣan'āny which states that the term dhikr here refers to verbal dhikr. Al-Ṣan'āny adds if one recites the verbal dhikr while also doing it in their heart, then it will become more perfect. The third attempt is to distinguish between what is right and what is wrong. The measuring instrument for knowing al-haqq (truth) and bāṭil (falsehood) refers to thoughts, not a person. Meanwhile, to know what is true and false, one must refer to kitābullah (The Book of Allah).